1989
DOI: 10.1115/1.3176197
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Investigation of Complicated Responses of a Two-Degree-of-Freedom Structure

Abstract: Recent theoretical studies indicate that whereas large excitation amplitudes are needed to produce chaotic motions in single-degree-of-freedom systems, extremely small excitation levels can produce chaotic motions in multi-degree-of-freedom systems if they possess autoparametric resonances. To verify these results, we conducted an experimental study of the response of a two-degree-of-freedom structure with quadratic nonlinearities and a two-to-one internal resonance to a primary resonant excitation of the seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 0 publications
2
27
0
Order By: Relevance
“…The results given above are similar to those presented by Nayfeh [15] for qmO(e) and .O=co. In fact it is found that the results of reference [15] are exactly obtained as co--*-(2 in equation (34), and the (small) fl2-term of equation (47) is neglected.…”
Section: Periodic Solutionssupporting
confidence: 79%
See 4 more Smart Citations
“…The results given above are similar to those presented by Nayfeh [15] for qmO(e) and .O=co. In fact it is found that the results of reference [15] are exactly obtained as co--*-(2 in equation (34), and the (small) fl2-term of equation (47) is neglected.…”
Section: Periodic Solutionssupporting
confidence: 79%
“…In fact it is found that the results of reference [15] are exactly obtained as co--*-(2 in equation (34), and the (small) fl2-term of equation (47) is neglected. The consequence, however, is that the instability boundary between regions B and D in Figure 5 tilts to the right, away from the results obtained when using both Mathieu-Hill theory and numerical simulations.…”
Section: Periodic Solutionsmentioning
confidence: 83%
See 3 more Smart Citations